Controlling diffusion in gold bonding materials for high reliability via microalloying of trace rare earth metals. (June 2023) - Zhang, Boning; Xu, Lai; Xiong, Kai; He, Junjie; Rong, Xuequan; Mao, Yong; Tang, Xiaozhi
Abstract: Diffusion plays a vital role in regulating microstructure evolution and properties of metallic materials. However, understandings of how microalloying affects diffusion kinetics in gold bonding materials remain far from comprehensive, which severely threatens the reliability of microelectronic devices in the big-data era. This problem persists challenging due to enormous difficulty in accurate and cost-effective experimental measurements. Here, first-principle based theoretical computations are performed to explore the control of diffusion at elevated service temperatures by trace rare earth (RE) microalloying in gold bonding materials. We identify the light lanthanides can stably bind excess vacancies and the efficacy to modulate vacancy/solute-vacancy evolution depends on the RE concentrations and ambient temperatures. Above critical doping concentrations, self- and impurity-diffusion can be simultaneously hindered. These findings successfully point to a rational microalloying strategy to withstand heat and a novel perspective on improving the service life-time of microelectronics packaging materials. Graphical abstract: Image, graphical abstract